Evolving Therapeutic Approaches for Diabetes: Harnessing the Benefits of Herbal Remedies in the Modern Era - Roy, Sukanta; Majumder, Shramana; Das, Sourav; Bhattacharjee, Senjuti; Bose, Anirbandeep; Mondal, Subhasish (Current Overview on Pharmaceutical Science Vol. 6, 2023)
This chapter will discuss the use of herbal medicines as a treatment approach for Diabetes Mellitus (DM), a disorder that is particularly common in the Asian subcontinent. Specifically, this chapter will focus on the treatment of Non-insulin-dependent Diabetes Mellitus (NIDDM) or Type 2 DM (T2DM). Herbal medicines have long been the backbone of the medicinal system in India, and this chapter will explore the original, novel, and ancient ways of treating the disorder. Various plants with anti-diabetic effects, such as catechu, basil, Ginko biloba, fenugreek, etc, will be discussed in detail. Furthermore, several marketed herbal products, such as Bitter gourd powder, episulin, Dia care, and much more, will be discussed. The chapter will explore the mechanisms of action of these herbal products and how they can be effective medications for the disorder. The aim of this chapter is to provide evidence that herbal products can be effective treatments for DM and to re-establish herbal drugs as a viable treatment approach